Prevalence and associated factors of illicit drug use among university students in the association of southeast Asian nations (ASEAN) - Siyan Yi; Karl Peltzer; Supa Pengpid; Indri Hapsari Susilowati (BMC, 2017)
Abstract Background Illicit drug use among university students has been recognized as a global public health issue in recent years. It may lead to poor academic performance that in turn leads to poor productivity in their later life. This study explores prevalence of and factors associated with illicit drug use among university students in the Association of Southeast Asian Nations (ASEAN). Methods This multi-country cross-sectional study was conducted in 2015 in Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand and Vietnam. A multi-stage cluster sampling was used to select undergraduate students from one or two universities in each country for self-administered questionnaire survey. Multivariate logistic regression analyses was performed to explore risk factors related to illicit drug use. Results Participants included 7,923 students with a mean age of 20.6 years (SD = 2.8), ranging from 18-30 years. The overall prevalence of frequent (≥10 times), infrequent (1-9 times) and ever (at least once) illicit drug use in the past 12 months was 2.2, 14.7, and 16.9%, respectively. After adjustment, male students were significantly less likely to be infrequent (1-9 times vs. never), but significantly more likely to be ever users compared to females. Compared to those living with parents/guardians, students living away from parents/guardians were significantly less likely to be frequent (≥10 times vs. never) and infrequent users. Students from lower-middle-income countries were significantly more likely to be frequent and infrequent users, but significantly less likely to be ever users compared to those from upper-middle or high-income countries. Students with poor subjective health status were significantly more likely to be frequent users compared to those who reported good subjective health status. Students who reported binge drinking in the past month were significantly more likely to be infrequent users, but significantly less likely to be ever users. Conclusions Our findings indicate that prevalence of illicit drug use among university students in the ASEAN region varied by country. Concerted social intervention programs should be designed to address related health and behavioral problems such as illicit drug use and alcohol drinking with particular emphasis on at-risk subgroups of this young population.